Deep listening: A composer's sound practice - Oliveros, Pauline 1932-2016 (New York iUniverse, 2005)
Deep Listening: A Composer's Sound Practice offers an exciting guide to ways of listening and sounding. This book provides unique insights and perspectives for artists, students, teachers, meditators and anyone interested in how consciousness may be effected by profound attention to the sonic environment .Deep Listening® is a practice created by composer Pauline Oliveros in order to enhance her own as well as other's listening skills. She teaches this practice worldwide in workshops, retreats and in her ground breaking Deep Listening classes at Rensselaer Polytechnic Institute and Mills College. Deep Listening practice is accessible to anyone with an interest in listening. Undergraduates with no musical training benefit from the practices and successfully engage in creative sound projects. Many report life changing effects from participating in the Deep Listening classes and retreats.Oliveros is recognized as a pioneer in electronic music and a leader in contemporary music as composer, performer, educator and author. Her works are performed internationally and her improvisational performances are documented extensively on recordings, in the literature and on the worldwide web.